2022
DOI: 10.1590/fst.10721
|View full text |Cite
|
Sign up to set email alerts
|

A review on the functional properties of fermented soymilk

Abstract: Soy products have been used for ages in various forms, including soymilk, soy cheese, tempeh, tamari, soy sauce, soy yogurt, and soy mayonnaise. They are rich in isoflavones, and their consumption is associated with several health benefits, especially protection from gastrointestinal disorders, cardiovascular diseases, and cancers (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Moreover, soy milk is naturally rich in essential nutrients, such as high-quality proteins, fibers, and isoflavones, which can serve as substrates for the growth and activity of probiotic bacteria within the intestinal environment [27,28]. Recent studies have demonstrated that soy milk can support the development and viability of several probiotic species, mainly belonging to the Lactobacillus and Bifidobacterium genera [27,29,30], thus allowing for the production of fermented products enriched with beneficial microorganisms able to enhance consumers' digestive and immune health. The influence of soy milk as a cultivation medium for probiotic bacteria has been explored in the literature [27,29,30].…”
Section: Production Of Organic Acids By Probiotics Grown In Soy-based...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, soy milk is naturally rich in essential nutrients, such as high-quality proteins, fibers, and isoflavones, which can serve as substrates for the growth and activity of probiotic bacteria within the intestinal environment [27,28]. Recent studies have demonstrated that soy milk can support the development and viability of several probiotic species, mainly belonging to the Lactobacillus and Bifidobacterium genera [27,29,30], thus allowing for the production of fermented products enriched with beneficial microorganisms able to enhance consumers' digestive and immune health. The influence of soy milk as a cultivation medium for probiotic bacteria has been explored in the literature [27,29,30].…”
Section: Production Of Organic Acids By Probiotics Grown In Soy-based...mentioning
confidence: 99%
“…Recent studies have demonstrated that soy milk can support the development and viability of several probiotic species, mainly belonging to the Lactobacillus and Bifidobacterium genera [27,29,30], thus allowing for the production of fermented products enriched with beneficial microorganisms able to enhance consumers' digestive and immune health. The influence of soy milk as a cultivation medium for probiotic bacteria has been explored in the literature [27,29,30]. The findings reveal that soy milk not only enhanced the growth of the tested probiotic bacteria but also promoted the production of beneficial metabolites, such as organic acids.…”
Section: Production Of Organic Acids By Probiotics Grown In Soy-based...mentioning
confidence: 99%
“…Soy products have been used for ages, and their consumption is correlated with additional health benefits (Kesika et al, 2022). The fermentation of water-soluble soy extract (WSSE) by lactic acid bacteria has been utilized to obtain fermented beverages as an alternative to improve the nutritional and sensory properties of soybean (Kesika et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Soy products have been used for ages, and their consumption is correlated with additional health benefits (Kesika et al, 2022). The fermentation of water-soluble soy extract (WSSE) by lactic acid bacteria has been utilized to obtain fermented beverages as an alternative to improve the nutritional and sensory properties of soybean (Kesika et al, 2022). The use of WSSE as a partial substitute for milk in the manufacturing of dairy products has been evaluated as an alternative to innovate and improve some quality aspects of the products (Park et al, 2005;Tsai et al, 2009;Šertović et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The fermented soymilk obtained by lactic acid bacteria fermentation has been studied and developed as a novel plant-based drink with a smooth texture and reduced beany flavor [ 12 ]. Meanwhile, its nutritional characteristics and health-beneficial properties have been developed for application [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%